Enteric and non-enteric adenoviruses associated with acute gastroenteritis in pediatric patients in Thailand, 2011 to 2017 - Kattareeya Kumthip (2019)
© 2019 Kumthip et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Human adenovirus (HAdV) is known to be a common cause of diarrhea in children worldwide. Infection with adenovirus is responsible for 2–10% of diarrheic cases. To increase a better understanding of the prevalence and epidemiology of HAdV infection, a large scale and long-term study was needed. We implemented a multi-year molecular detection and characterization study of HAdV in association with acute gastroenteritis in Chiang Mai, Thailand from 2011 to 2017. Out of 2,312 patients, HAdV was detected in 165 cases (7.2%). The positive rate for HAdV infection was highest in children of 1 and 2 years of age compared to other age groups. HAdV subgroup C (40.6%) was the most prevalent, followed by subgroups F (28.5%), B (20.6%), A and D (4.8% each), and E (0.6%). Of these, HAdV-F41 (22.4%), HAdV-C2 (18.2%), HAdV-B3 (15.2%), and HAdV-C1 (13.3%) were the most common genotypes detected. HAdV infection occurred throughout the year with a higher detection rate between May and July. In conclusion, our study demonstrated the infection rate, seasonal distribution and genotype diversity of HAdV infection in children with diarrhea in Chiang Mai, Thailand over a period of 7 year. Not only enteric adenovirus (F40 and F41) but also non-enteric adenovirus (B3, C1, C2) may play an important role in gastroenteritis in this area. The information will be beneficial for the prevention and control of HAdV outbreaks in the future.